Solvent extraction and spectrophotometric determination Of ni(ii) by using 5-bromo salicylidene-2-aminothiophenol As an analytical reagent - SANJAY K. PATIL, (International Journal of Pharma and Bio Sciences, 2017)
Solvent extraction and spectrophotometric determination of metal ions are most versatile methods used for the removal, separation and concentration of metallic species from aqueous media. A spectrophotometric method has been developed for the determination of Nickel, Ni(II) using 5-bromo salicylidene-2-aminothiophenol as novel extractive reagent. The reagent forms a coloured complex which has been quantitatively extracted into n-Butanol at pH 7.8. The method obeys Beer’s law over a range of 1 to 10 ppm. The molar absorptivity is 7428 L mol-1cm-1 and Sandell’s sensitivity is 0.02083 µg/cm2 respectively. The proposed method is very sensitive and selective. This method has been successfully applied for the determination of nickel from various alloys, synthetic mixtures and vegetable oil samples.